The road to organic growth : how great companies consistentlyu grow marketshare from within - Hess, Edward (New York : McGraw-Hill, 2007)
Why is Organic Growth a Smart Long-Term Strategy for Your Company? A rigorous two-year study of the top 800 value-creating public companies found that growth generated internally through a commitment to customer satisfaction, employee engagement, and profitability resulted in consistent employee retention, stock value improvements, and better returns on investment. In The Road to Organic Growth, Edward Hess shares the full results of his breakthrough study, providing fresh, and often-surprising perspectives on what it really takes to foster organic growth. Using instructive examples from leading companies such as SYSCO, Best Buy,Tiffany & Company, Outback Steakhouse, and Stryker Corporation, Hess reveals the strategies these trailblazers used to achieve long-term growth from within. Drawing upon original research, interviews, and in-depth corporate studies, Hess identifies the six keys to achieving organic growth and-most important-explains how to seamlessly and consistently incorporate them into a formula for sustainability and competitive advantage to Develop a simple, easy-to-understand business model and growth strategy Be entrepreneurial at the point of customer contact Measure everything-from finances to operations to behaviors Build an engaged, loyal, and multi-talented people pipeline Find humble, internally-focused operators to lead your company Be an execution and technology champion The Road to Organic Growth proves that you can build a sustainable, successful business without the expense of acquisitions, financial manipulations, or devaluing your employees. By exceeding customer expectations, building an employee-centric organization, and focusing intensely on measurement and performance, your company will achieve consistent, solid growth from within.
Why is organic growth important -- Discovering the DNA of organic growth : the SYSCO story, an entrepreneurial market leader -- The organic growth winners : interesting facts -- An elevator-pitch business model : the Stryker story, a simplistic focus on 20 percent growth -- Instill a small company soul into a big company body : the Outback Steakhouse story, the power of ownership -- Measure everything : the Best Buy story, how to keep a successful company engaged -- Build a people pipeline : the TSYS story, a culture of the heart -- Leaders : humble, passionate, focused operators : the Tiffany & Co. story, growth without compromise -- Be an execution and technology champion : the American Eagle story, the merger of fashion and technology.
Includes bibliographical references (p. 191-202) and index.
Keywords: Industrial management -- United States; Success in business -- United States